III Workshop on Sustainable Development in Mountain Environments and II International Conference on Research for Sustainable Development in Mountain Regions: Mountains 2018: book of abstracts - Aquino, Adriana Maria de (2018)
I am very pleased to have been asked to write this Preface, to introduce the first major international mountain science meeting to take place in Brazil, contributing to our growing knowledge and understanding of mountain issues. In October 2016, I participated in ‘Mountains 2016’ in Bragança, Portugal (http://cimo.esa.ipb.pt/mountains2016/). This attracted 182 delegates from 32 countries and was addressed by the Minister of Science, Technology and Higher Education of Portugal. He showed particular interest in one of the key outcomes: the launching of the Lusophony Mountain Research Network – Lumont (http://cimo.esa.ipb.pt/LuMont/index.php/pt/) to encourage exchange among Portuguese-speaking scientists working in the mountain areas of their countries. The establishment of this network provided additional support for Brazil to organize ‘Mountains 2018’. ‘Mountains 2018’ is taking place from 11 to 15 December 2018 in the mountain town of Nova Friburgo, in the state of Rio de Janeiro, close to Pico Maior (2,366 m), the highest point of the 1,500 kilometre-long Serra do Mar. As you will see from the abstracts in this book, the participants in ‘Mountains 2018’ will include scholars, professionals, policy makers and others involved with multiple aspects of the mountain world: at least 200 people from about 30 countries. Over a hundred of the people will be from Brazil; on one hand, this will allow all the visitors to learn about the mountains of Brazil and interact with people working in them; on the other hand, it will enable the Brazilian participants to place their challenges and experiences in an international context. The aim of ‘Mountains 2018’ is to stimulate and disseminate knowledge based on lessons learned from scientific research and practical experiences related to the use and challenges of promoting sustainable development in mountain areas, including how mountains can contribute to the Sustainable Development Goals. The event includes two parts: the III Workshop on Sustainable Development in Mountain Regions; and the II International Conference on Research for Sustainable Development in Mountain Regions. The Workshop will focus on practical experiences related to sustainable development in mountain regions, gathering professionals and other stakeholders actively working towards this urgent goal. The Conference will discuss issues related to scientific research and perspectives to enhance and disseminate knowledge about mountains. Whether or not you are attending ‘Mountains 2018’, I hope that this book will provide you with new knowledge and insights about the mountains of the word, and that you will be able to apply these in your own mountains.